Rule-based system for quality of life evaluation in socio-cultural field - Šanda Martin; Křupka Jiří (SciTePress - Science and Technology Publications, 2016)
This article deals with the quality of life in European Union. The objective of this article is to analyse the possibilities of quality of life evaluation on the European level based on selected indicators. For evaluation of quality of life is used expert system and fuzzy sets. User gives the value of a total of thirteen indicators of socio-cultural field, which are divided into three areas. The indicators are selected from several methodologies for evaluating the quality of life and are divided into areas with similar principles and characteristics. Selected methodologies are Active Aging Index, Eurofound, the Economist Intelligence Unit and the Better Life Index.The expert system determines rating for each area and for total rating of quality of life for the selected country. In the conclusions of this paper are other options for adjustments and expansion.
Pravidlový systém pro hodnocení socio-kulturní oblasti kvality života
Keywords: evaluation; fuzzy; indicators; quality of life; rules; rule-based system; hodnocení; fuzzy; kvalita života; ukazatele; pravidla; pravidlový systém